Biochemical studies of whaling problems : 1 - Valsø, Jakob; Pedersen, Torbjørn (I kommisjon hos Dybwad, 1938)
Inneholder: Jakob Valsø: The Hypophysis of the Blue Whale. (Balaenoptera musculus L.). Macroscopical and Microscopical Anatomy and Hormone Content. Torbjørn Pedersen: On the Course of Hydrogenation in the Industrial Hardening of Whale Oil with Nickel Formate Catalyst.
Publication Title: Hvalrådets skrifter : scientific results of marine biological research
Keywords: Sørishavet; biokjemi; biologi; farmakologi; hvaler; hvalfangst; hvalolje; pelagisk

Omkring hvalfangsten - Bogen, Hans (Samtiden: tidsskrift for politikk, litteratur og samfunnsspørsmål, 1936)
Publisher: Aschehoug
Keywords: Sørishavet; hvalfangst; hvalfangstnæring; hvalolje; pelagisk; økonomi

Forgiftningsfaktorer ved katalytisk hydrering av tran - Lund, Jakob (I kommisjon hos Dybwad, 1931)
Publication Title: Skrifter (Det Norske videnskaps-akademi i Oslo : trykt utg.)
Keywords: Sørishavet; biokjemi; hvaler; hvalfangst; hvalolje; pelagisk